The development of children's teaching varies by cultural input: evidence from China and the U.S. - Ye, Nina Ni; Cui, Yixin Kelly; Ronfard, Samuel; Corriveau, Kathleen H. (Frontiers in Developmental Psychology, 2025)
Teaching, often seen as a natural cognitive ability, is also shaped by cultural environments. This study compared the teaching strategies among 146 3- to 7-year-old children (81 females) from the U.S. (n = 52, White) and China (traditional preschool n = 49, Asian; “westernized” preschool n = 45, Asian). Children taught a board game to learners with varying knowledge levels. We measured children's false belief and knowledge attribution and coded three teaching strategies: verbal, contrastive, and contingent. Results showed that children from traditional Chinese preschools were less likely to engage in verbal and contingent teaching than their U.S. and “westernized” Chinese counterparts. Knowledge attribution predicted teaching strategies across cultures. These findings underscore the influence of cultural input on teaching strategies.